A study of the application of adaptive minimum bit error rate algorithms for WCDMA - Tai, Tyrone W. (2007)
This research aims to use the Adaptive Minimum Bit Error Rate (AMBER) algorithms for Wideband Code Division Multiple Access (WCDMA) systems. AMBER and Normalized AMBER (NAMBER) algorithms for WCDMA systems are derived and implemented. Its Bit Error Rate (BER) performance is measured using a WCDMA Frequency Division Duplex (FDD) Downlink Physical Layer model. The new methods are compared to the original WCDMA system and the NLMS Adaptive Combiner (AC). Results show around 5 dB performance gain over the single antenna system, and a 2 dB performance gain over the NLMS AC system in an Additive White Gaussian Noise channel at a Bit Error Rate (BER) of 10-2.5. However, due to BER estimation algorithm used, the current implementation works only for BER values of 0 to 0.5. The system diverges under conditions that cause BER values of 0 to 0.5 The system diverges under conditions that cause BER values to reach 0.5 or higher (e.g. Lower signal power, poor initial weight selection). Furthermore, complex computation requirements of the algorithms may render it impractical for widespread use. Alternative implementations have to be investigated.